Religious Moderation for Police Officer Education - Wahdan Sanur Tarihoran; Ahmad Tihami; Ahmad Qurthubi (Syntax Corporation Indonesia, 2022)
Education can actually shape the character of students into human beings who are increasingly devoted to God Almighty as created beings and caliphs (leaders) without discriminating against SARA, so that all forms of education carried out are directed to achieve the goal of human creation as well as the purpose of education. alone. This study aims to explain the management of Islamic religious education at the Setukpa Lemdiklat Polri which is responsible for educating Polri officers (leaders) to serve as first supervisors in the Indonesian National Police. To describe the process of religious education management in the Setukpa Lemdiklat Polri used qualitative research methods. Data was collected by observing the educational component of religious activities, interviews with spiritual coaches, coaches/caregivers and education administration managers. Data was also obtained from documentation of religious activities carried out at the Setukpa Lemdiklat Polri. The results showed that religious moderation for the education of police officers was carried out in the implementation of spiritual development, the character of Kebhayangkaran, learning material for group attitudes and values, the application of management activities was found in the practice of worship and student organization management through structured and measurable parenting patterns.